2021
DOI: 10.1021/acs.orglett.1c02460
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Distal m-C–H Functionalization of Arylacetic Acid Derivatives

Abstract: Herein, we present m-C–H olefination on derivatives of phenylacetic acids by tethering with a simple nitrile-based template through palladium catalysis. Notably, the versatility of the method is evaluated with a wide range of phenylacetic acid derivatives for obtaining the meta-olefination products in fair to excellent yields with outstanding selectivities under mild conditions. Significantly, the present strategy is successfully exemplified for the synthesis of drugs/natural product analogues (naproxen, ibupr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 60 publications
(68 reference statements)
0
19
0
Order By: Relevance
“…Glucose pentaacetate was selectively hydrolyzed at the anomeric position using a known method to give glucose tetraacetate 7. 12 This product was used without purification in the next step. Treating a mixture of catechol and tetraacetate glucose 7 with boron trifluoride etherate effectively yielded the desired glucoside 6 in a 44% yield over two steps.…”
Section: Paper Synthesismentioning
confidence: 99%
“…Glucose pentaacetate was selectively hydrolyzed at the anomeric position using a known method to give glucose tetraacetate 7. 12 This product was used without purification in the next step. Treating a mixture of catechol and tetraacetate glucose 7 with boron trifluoride etherate effectively yielded the desired glucoside 6 in a 44% yield over two steps.…”
Section: Paper Synthesismentioning
confidence: 99%
“…To this context, we recently developed 2-cyano-2,2-di-isobutyl acetic acid as the first aliphatic nitrile template for the remote meta -C–H olefination of alcohols bearing aromatic rings. , To the continuation of our endeavors toward C–H activation and inspired by recent research work on meta -C–H activation assisted by directing group templates, herein, we report the design of an unprecedented nitrile-based aliphatic template that permits C–H bond olefination of dihydrocinnamic acids at remote meta -position, thus providing a highly adaptable method for rapid construction of dihydrocinnamic acid frameworks that are of importance in medicinal chemistry and drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…3 a Later, various research groups reported different kinds of nitrile-based directing groups for the meta -C–H bond activation of aromatic substrates. Several reports 3 have been documented in the literature for meta -C–H bond activation using the nitrile directing group, generated from 2-cyanophenol, triazene-attached cyanobenzene, 2-cyanoaniline derivatives, the 2-cyanophenethyl sulphonamide derivative and the silicon-tethered nitrile group (Scheme 1a). However, the nitrile-directing group derived from 2-cyanobenzoic acid has not been explored much.…”
mentioning
confidence: 99%
“…A plausible catalytic cycle is described based on previous reports. 3 First, the nitrile group coordinates with Pd( ii ) and activates the aryl meta -C–H bond of cinnamate 1a , which forms the 13-membered palladium complex ( I ). Subsequently, olefin 2a coordinates with the palladium complex ( I ) leading to intermediate II , followed by 1,2-migratory insertion to give intermediate III .…”
mentioning
confidence: 99%